Post-ethnographic museums: Changing relationships between museum and anthropology in France - Benoît de L'Estoile (Anuac, 2016)
The article analyses the contemporary transformations of the relationships between anthropology and museums in France in the wake of the opening in recent years of the Musée du quai Branly, the Musée des Civilisations de l'Europe et de la Méditerranée (MUCEM), and the reopening in 2015 of the Musée de l’Homme. The relationship between museums and anthropology, historically tighter in France than in other national contexts, explains the intensity of reactions triggered by these transformations. Retracing the historical transformations of ethnographic museums, and especially the ideal of the ‘museum-laboratory’, shows the enduring role of the naturalist, encyclopedic paradigm. The exhaustion of the natural history paradigm, in the Muséum National d'Histoire Naturelle in Paris as in ethnographic museums, has produced a change in the role of museums, with a shift from a museological discourse under the spell of science and rationalism to a more aesthetic and emotional approach. However, the new Musée de l'Homme embodies a revival of the naturalist and evolutionist paradigm. These new museums, which can be defined as 'post-ethnographic', have avoided a critical reflexive confrontation with history and colonial legacies. Meanwhile French anthropology is now facing the challenge of reinventing itself as a ‘post-museum anthropology’.